Direct displacement effects of labour market programmes: the case of Sweden - Matz Dahlberg; Anders Forslund (Institute for Labour Market Policy Evaluation (IFAU), 1999)
Using a panel of 260 Swedish municipalities over the period 1987-1996, this paper investigates the direct displacement effects of active labour market programmes (ALMPs). Compared to earlier studies on this topic, we have more and better data. From our GMM estimations, we find that (i) there are direct displacement effects from those ALMPs that generate subsidised labour (in the order of approximately 65 percent), but there seems to be no (significant) displacement effects from training, (ii) most ALMPs seem to increase labour force participation, and (iii) the adjustment to the optimal level of employment seems to be sluggish. A consequence of (ii) is that the earlier studies have overstated the displacement effects (since they nomalised with the labour force).
Keywords: J30; 330; Labour market programmes; Displacement effects; GMM estimation